Developing a sport - and athlete - specific warm up exercise for enhanced power output during sprint kayaking using post activation potentiation - Yong, Grace Zhi Wei (2018)
Post activation potentiation (PAP) is a phenomenon whereby performing resistance exercises at near maximal loads for a brief moment can improve ensuing force output after a specific latency period. This phenomenon has often been researched on land-based exercises such as performing heavy squats prior to counter-movement jumps (Gourgoulis, Aggeloussis, Kasimatis, Mavromatis, & Garas, 2003). Less is understood about the utility of sport-specific resistance exercises to induce PAP for performance enhancement especially in the domain of water sports such as kayaking. KSRE, commonly used in kayaking trainings, is made by slinging a string of tennis balls under the hull, increasing wetted surface area and hence drag force while the kayak is being propelled forward. This study aims to match SSAR and KSRE load using mathematical methods and computational simulations, as well as to find out whether the KSRE is able to induce PAP and improve 200 m kayak performance. It was hypothesized that increasing SSAR strength will require a higher KSRE load to induce PAP, and KSRE is able to increase power outputs and improve 200 m timings. Thirteen kayakers who have at least three years of paddling experience were recruited. Their maximal strength on the single-seated arm row (SSAR) were and optimal latency period to peak power were determined during the on-land session. During the on-water session, they performed KSRE prior to the 200 m time trial. Significant improvement in 200 m timing, top speed, and total average power were found. Coaches could possibly implement this warm-up protocol prior to athletes’ race events to enhance their sport performance.